FORMATION OF SUGAR BEET PRODUCTIVITY WITH APPLICATION OF BIOLAN GROWTH REGULATOR IN CENTRAL UKRAINE - Kulyk H. А.; Trykina, N. M.; Malakhovska V. О. (Scientific Progress & Innovations, 2022)
The issues of efficiency of Biolan growth regulator in sugar beet cultivation in the Central part of Ukraine are considered in the article. It is known that plant growth regulator is one of the factors increasing productivity of sugar beets. Growth regulators are recognized as products that in small doses can significantly increase productivity of root crops, which is economically feasible to use. To date, a significant amount of these products is accessible, and scientists are constantly conducting research to study most effective ones, their standards and combinations of applications in certain soil and climatic conditions. Each field crop has its own potential level of productivity, which is genetically determined. Plants can realize their productive potential if they have appropriate living conditions. One of such conditions is the use of growth regulators as preperations that occupy a prominent place in the technology of sugar beet cultivation and provide significant improvement in productivity, sugar content of root crops and conditional yield of sugar per unit area. We conducted research to study the effect of growth regulator Biolan on the formation of sugar beet productivity while using the product for both seed treatment and crop spraying. The application of Biolan growth regulator for sugar beet seed treatment under favorable weather conditions provides an increase in field germination by 10.9 %. According to the dynamics of growth of leaf surface area, we recorded an increase in the indicator due to the integrated application of Biolan growth regulator. Thus, for the period of the most active vegetation of the culture, the leaf surface area with the combined use of Biolan was 16.2 % more than the control. Application of Biolan growth regulator in the cultivation of sugar beets has increased the productivity of root crops. We found that the most effective composition was with seed treatment and spraying crops, where the increase in productivity was 3.8 t/ha, sugar content 0.4 % and sugar yield was 0.83 t/ha.